Pengembangan Modul Biologi berbasis Reasoning and Problem Solving disertai Concept Mapping Tipe Network Tree pada Materi Pencemaran Lingkungan untuk Memberdayakan Keterampilan Proses Sains dan Kemampuan Mengevaluas - ALQURIYAH, YUSROH; SUDARISMAN, SUCIATI; PRAYITNO, BASKORO ADI (Bioedukasi: Jurnal Pendidikan Biologi, 2014)
The objectives of this research and development are to investigate: 1) characteristic of biology module based on reasoning and problem solving (RPS) with network tree concept mapping (CM); 2) feasibility of biology module based on RPS with network tree CM to empower science process skills and evaluation abilities; 3) effectiveness of biology module based on RPS with network tree CM toward science process skills; and 4) effectiveness of biology module based on RPS with network tree CM toward evaluation abilities. This research used the Research and Development (R&D) which referred to the model claimed by Borg & Gall (1983) with some modifications. The samples of the research included those of preliminary field testing which involved 7 validators, those of main field testing that involved 10 students, and those of operational field testing which involved 32 students. The operational field testing used the one group pretest and posstest design. The data of research were gathered through questionnaire, observation, interview, and test. The data of science process skills and evaluation abilities were tested by means of paired sample t-test and calculated by using normalized gain score. The results of research showed that: 1) the characteristics of biology module based on RPS with network tree CM are as follows: (a) the development uses the model claimed by Borg & Gall with some modifications (research and information collecting, planning, development of preliminary form of product, preliminary field testing, main product revision, main field testing, operational product revision, operational field, final product revision, and dissemination and implementation); (b) module developed by RPSsyntax(read and think, explore and plan, select strategy, find and answer, dan reflect and extend);(c) module with network treeCM as a techniques  of expansion and strengthening concept; (d) the learning activities in the module can empower science process skills and evaluation abilities; 2) the score of feasibility of biology module based on RPS with network tree CM is 3.27, which is in the very good category; 3) the biology module based on RPS with network tree CM is effective to empower science process skills as indicated by the N-gain score of 0.58, which is in the moderate category; and 4) the biology module based on RPS with network tree CM is effective to empower evaluation abilities as signified by the N-gain score of 0.30, which is in the moderate category.